TRENDS IN ORGANIC RASPBERRY MARKET IN UKRAINE AND WOLRDWIDE - Rostyslav FEDIV; Iryna FEDIV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper is the analysis of the main trends in organic agriculture, based on the research of the world markets of organic agricultural products and specificities of the organic raspberry cultivation in Ukraine. Definitely Ukraine has credible prospects for gaining leading positions on global market of the organic production. In the paper there were determined the main risks in doing business, which is related to the organic raspberry cultivation, and which could be classified into three main groups: natural and climate risks;manufacturing risks and market risks.